CRUDE OIL DEGRADATION POTENTIAL BY HYDROCARBON-UTILIZING MICROBES: A REVIEW - Yarima, Safina Abdullahi; Farouq, Ahmadu Ali; Fardami, Aminu Yusuf; Bunza, Abubakar Bello; Abdullahi, Sherif; Ibrahim, Umar Balarabe; Banye, Maryam Amiru (FUDMA JOURNAL OF SCIENCES, 2025)
Globally, environmental pollution by crude oil is one of the most frequently encountered problem faced by the world today as a result of industrial activities, oil spill, and accidental occurrence, among others. Primarily, crude oil are composed of hydrocarbons, which are molecules composed of only carbon and hydrogen atoms. This review aim to present the indispensable role played by hydrocarbon-utilizing microorganisms in the degradation of crude oil, thereby reducing their pollution in the environment. The degradation of hydrocarbon is a complex action primarily mediated by microorganisms that utilize hydrocarbons as carbon sources via employing series of enzymatic pathways to break down these otherwise persistent environmental pollutants. Beyond enzymatic actions, biofilm formation and biosurfactants production are among the mechanisms used in these crude oil degradation. Microorganisms, including Penicillium, Nocardia, Aspergillus, Corynebacterium, Pseudomonas and Bacillus species are among the most frequently reported microorganisms capable of degrading crude oil pollutants. Several factors which influences these microbial action such as pH, inhibitors, nutrients availability, moisture and temperature always limits these degradation process. As reported by many scholars, bioremediation of crude oil by utilizing hydrocarbon degrading microorganisms has now been employed due to their inexpensive and non-toxic nature. Thus, bioremediation of crude oil by the usage of hydrocarbon-utilizing microorganisms represents a wonderful approach for decreasing the environmental impact of crude oil.  Therefore parameters such as temperature, nutrient levels and pH should be optimized to enhance biodegradation efficiency.
Keywords: Crude oil; Hydrocarbon-utilizing Microorganisms; Hydrocarbon; Enzyme; Degradation